An IoT-Based Implementation with Node-RED for Real-Time Monitoring and Early Warning of Laboratory Energy Consumption via Telegram - Damayanti, Annisa Maulidia; Sarifudin; Nor, Syafriyadi (Universitas Muhammadiyah Surakarta, 2026)
Accurate and responsive monitoring of electricity consumption plays a crucial role in improving energy efficiency. This study develops an Internet of Things (IoT)-based kWh meter monitoring system equipped with real-time early warning features when room-level energy consumption exceeds a predefined threshold. The implementation was carried out in two laboratories, integrating Modbus RTU (Remote Terminal Unit) for data acquisition, MQTT (Message Queuing Telemetry Transport) as the communication protocol, Node-RED for integration and visualization, and SQLite as the database. Automatic notifications are delivered via Telegram when the total power consumption surpasses 2000 W. Experimental results demonstrate that the system can reliably record data at 30-second intervals, with voltage and frequency remaining stable in accordance with nominal standards, while current and total active power reflect actual load conditions. The power factor remained close to 1, indicating high energy efficiency. The system has proven effective in providing timely early warnings, enabling operators to respond promptly to increases in energy consumption. The main contribution of this research is the simple yet effective integration of Modbus RTU, MQTT, Node-RED, and SQLite for laboratory-scale energy monitoring with real-time notifications, which can be potentially expanded to a multi-building scale.